Parental Involvement of African Migrants in Multicultural Israeli Education Settings - Dolly Eliyahu-Levi (MDPI AG, 2024)
This study aimed to examine the cultivation of mutual and beneficial relationships between educators and African asylum-seeker parents, focusing on the first level of Hoover-Dempsey's parental involvement model, in Tel Aviv, Israel. This qualitative-phenomenological research allows the personal and authentic voices of fifteen educators and twenty parents to be heard. The findings indicate, on the one hand, differences between educators and parents when it comes to the meanings and roles of parental involvement. However, this involvement depends mainly on educators overcoming a feeling of racial-national superiority. Despite parents' wishes to cooperate, their involvement is limited because involvement requires financial resources, free time, and the ability to communicate in the dominant language.